Types of support expected by women treated due to gynaecological reasons during the peri-operative period - Lewicka, Magdalena; Wdowiak, Artur; Sulima, Magdalena; Stawarz, Barbara; Bakalczuk, Szymon; Bakalczuk, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : Women at the peri- and post-menopausal age who are qualified for surgical procedures for gynaecological reasons are exposed to specific emotional problems related with the necessity to perform the surgery. Therefore, they often expect various types of support. A characteristic feature of this support is an exchange of emotions, information, instruments for action and tangible property. Aim of the study : The objective of the study was to perform an analysis of the type of support expected during the peri-operative period by women treated for gynaecological reasons. Material and methods : The study covered 232 women at the pre- and peri-menopausal age who received surgical treatment for various gynaecological reasons. The study was carried out using an author-designed questionnaire form. The results of the study obtained were analysed statistically. The p values p < 0.05 were considered statistically significant. Results : It was found out that respondents who had university education significantly more frequently (p < 0.05) expected information and instrumental support, compared to those with elementary/elementary vocational or secondary education level. In turn, patients who were married significantly more often expected emotional and information support, compared to those who were single. The respondents who had undergone a surgical procedure with considerable tissue injury significantly more frequently (p < 0.05) expected material support than women who had undergone surgery with moderate tissue injury. Conclusions : The education level and marital status of patients determined the expectations of support during the peri-operative period, whereas patients’ age and category of surgical procedure did not have any effect on the expectations of support during this time.